2010
DOI: 10.1016/j.cbpa.2010.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular injection of orexin-A, but not orexin-B, induces arousal of layer-type neonatal chicks

Abstract: In order to determine if orexins affect arousal in neonatal chicks, we intracerebroventricularly (ICV) injected either orexin-A or orexin-B to layer and broiler type chicks (Gallus gallus) and measured their behaviors and food intake following injection. Layer chicks treated with orexin-A at 0.2 and 2.0 nmol had increased arousal but their food intake was not affected. However, arousal was not affected in broiler chicks treated with orexin-A, but they spent less time feeding. When orexin-B was administered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Food intake was not affected by any treatment in the present study (saline, 2.376 ± 0.696; orexin-A, 1.189 ± 0.256; clorgyline, 0.770 ± 0.191; orexin-A + clorgyline, 1.213 ± 0.432), which supports previous reports in which orexin-A did not alter food intake in chicks [5,8].…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Food intake was not affected by any treatment in the present study (saline, 2.376 ± 0.696; orexin-A, 1.189 ± 0.256; clorgyline, 0.770 ± 0.191; orexin-A + clorgyline, 1.213 ± 0.432), which supports previous reports in which orexin-A did not alter food intake in chicks [5,8].…”
supporting
confidence: 80%
“…Recently, we reported that orexin-A increased arousal in layer, but not broiler, chicks and that orexin-B is not likely to be involved in chick sleep/wake cycles [8]. Possible mechanisms associated with these behavioral affects may involve the hypothalamic-pituitary-adrenal (HPA) axis and/ or activation of monoamine neurons.…”
mentioning
confidence: 99%
“…Interestingly, orexin-A had no effect on arousal in broiler chicks however they spent less time feeding. Additionally, orexin-B had no effect on arousal and food intake neither in layer nor broiler [71] . As seen, orexin has different effects in domestic birds.…”
Section: Orexinmentioning
confidence: 78%
“…The differential responses to orexins in the two strains can related to variances in their receptors. Orexin-A is a ligand of both OX 1 R and OX 2 R whereas orexin-B activates only OX 2 R. Also, OX 1 R is associated with the Gq subclass of G proteins while OX 2 R is likely associated with the Gq and Gi/o [71] . In conclusion, presumably orexins induce feeding behavior acts via different neurological pathways in mammals and birds.…”
Section: Orexinmentioning
confidence: 99%
“…Both orexin and its receptor were expressed in chicken brain and gonads (testis and ovary) (49). Central administration of orexin did not affect feed intake in neonatal chickens (24), and its effects on sleep/wakefulness cycle is still controversial (33,34,45). The localization of orexin and its receptors in chicken peripheral tissues, such as testis, ovary, stomach, and intestine (3, 49), indicates that orexin system may have other physiological functions rather than the regulation of feeding behavior.…”
mentioning
confidence: 98%